CURRENT TRENDS IN PRESCRIBING PATTERN OF ANTI-MIGRAINE DRUGS IN PATIENTS OF MIGRAINE AT A TERTIARY CARE TEACHING HOSPITAL - Soni, G.; Jain, S.; Rathi, P.; Goswami, P. (International Journal of Medicine and Medical Research, 2022)
Background. An inappropriate prescribing pattern of antimigraine drugs by doctors may often encourage inappropriate self-medication by patients because of the asymmetry of medical information. Objective. The study is aimed to assess the current trends in prescribing patterns of anti-migraine drugs, rationality of prescription, and pattern of migraine severity in patients of migraine. Methods. A cross sectional study was conducted at a tertiary care teaching hospital. All the prescribing details including patient’s demographic details, diagnosis, details of drug therapy (drug name, dose, duration, and frequency) were recorded. Rationality of prescription was assessed using the WHO core drug prescribing indicators and the pattern of severity of migraine was assessed using MIDAS scoring system. Results. Out of 85 patients, 71 were female (83.5%), mostly around 21-30 years of age, and 27 (31.7%) patients had other comorbidities. Naproxen was the most commonly used NSAID for termination of acute migraine attack (15.3 %). The most common drugs prescribed for prophylaxis included beta adrenergic blockers (Propranolol, 14.66%), antidepressants (Amitriptyline, 9.33% and Fluoxetine 3.33%), and antipsychotics (Prochlorperazine, 4.66%). Domperidone (17.30%) was the most commonly prescribed antiemetic. Prescription of triptans was low (2.66%) with Rizatriptan as the most commonly prescribed triptan. Conclusions. The current study revealed that further improvements are required in prescribing practices especially in average number of drugs per prescription, prescription of drugs with generic names, and prescription of drugs of the essential drugs list.